Quasi-deterministic population dynamics in stochastic coupled maps - Gutierrez, Javier Armando (2015)
We studied the stochastic dynamics of coupled map lattices for small local populations. Quasi-deterministic dynamics is lost when considering one isolated population or two populations linked by dispersal. In a one-dimensional ring linked by closest neighbors some intermittent synchronization is observed. Finally we show that in two-dimensional lattices long-term synchronization take place above a critical value of the dispersal probability and the system displays a quasi-deterministic dynamics.